Observing Indonesia's Agrarian Conflict During The Covid-19 Pandemic - Indainanto, Yofiendi Indah; Nasution, Faiz Albar; Saraan, Muhammad Imanuddin Kandias (Journal of Peasants' Rights, 2022)
The Covid-19 epidemic has caused problems, especially in the economic field, which has an impact on the increasing number of residents at the local, national, and even global levels. It is also a health catastrophe throughout 2020. Long-term social distancing laws and restrictions on human movement and activities have rendered economic centers inoperable. Unusual events such as pandemics and reported weak economic growth cannot slow or even limit the rate at which companies acquire community land. According to the community, PSBB means complying with the government's request for restraint and creating a conducive environment by severely limiting mobility and activities outside the home. Meanwhile, Large-Scale Social Restrictions have become a driving force for the widespread appropriation of agrarian resources for large groups of companies with agrarian roots. Obviously, when the pandemic crisis is most severe and Large-Scale Social Restrictions are applied intensively, agrarian conflicts increase. Therefore, during the COVID-19 outbreak, agrarian disputes in Indonesia are very important to watch out for.